Correlation of drilling damage with mechanical strength: A geometrical approach - Durão, Luís Miguel (2017)
Nowadays composites are one of the most interesting groups of materials with applications in several technologically advanced fields like aeronautics, automotive or medicine among others. The great demand for this material comes from its low weight and high specific strength resulting in a good option for several demanding uses. One of the main advantages is related to the ability to produce parts in a near-net shape. However, assembly requirements normally include secondary operations like drilling. The resulting damage can affect the mechanical properties of the material questioning product reliability. In this work the authors present a comparative study of different combinations of tools, cutting speeds and feed rates associated with a method of image analysis that includes fractal dimension, a geometrical feature of the damaged region. This mathematical feature accounts for the irregularity of the damage boundary that can act as a stress concentration factor, thus causing mechanical strength reduction. Results include the presentation of a damage assessment model that could help on the correlation between the damaged region and the mechanical properties, including the contribution of the fractal dimension.